1994
DOI: 10.1021/bi00175a007
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Base Composition, Base Sequence, and Duplex Structure on DNA Hydration: Apparent Molar Volumes and Apparent Molar Adiabatic Compressibilities of Synthetic and Natural DNA Duplexes at 25.degree.C

Abstract: Using high-precision densitometric and ultrasonic measurements, we have determined, at 25 degrees C, the apparent molar volumes, phi V, and the apparent molar compressibilities, phi KS, of five natural and three synthetic B-form DNA duplexes with varying base compositions and base sequences. We find that phi V ranges from 152.0 to 186.6 cm3 mol-1, while phi KS ranges from -73.0 x 10(-4) to -32.6 x 10(-4) cm3 mol-1 bar-1. We interpret these data in terms of DNA hydration which, by the definition employed in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
125
3

Year Published

1997
1997
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(139 citation statements)
references
References 53 publications
(82 reference statements)
11
125
3
Order By: Relevance
“…Different studies looked at the effect of hydrostatic pressure, e.g., the stability of hairpins, B-DNA, the stalling of transcription elongation complexes [56][57][58][59][60][61]. The melting temperature T c seems to depend on the hydrostatic pressure, P , only at a very high P .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different studies looked at the effect of hydrostatic pressure, e.g., the stability of hairpins, B-DNA, the stalling of transcription elongation complexes [56][57][58][59][60][61]. The melting temperature T c seems to depend on the hydrostatic pressure, P , only at a very high P .…”
Section: Resultsmentioning
confidence: 99%
“…Besides the conjugate pairs (T, S), and (g, x), there could be other types of external forces, e.g., isotropic hydrostatic or osmotic pressure affecting the volume of the polymer, and a stretching force (f ) that distorts and elongates the chain. Although there are evidences of hydrostatic or osmotic pressure affecting protein-DNA interaction [56][57][58][59][60][61], there is only a very weak effect on the melting of DNA. In contrast, a stretching force may lead to an "overstretching" transition where the length of the DNA increases by a factor of 1.7 [8,17,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…24 From such studies the following picture emerges: In general, water in the hydration layer around DNA is less mobile 61,62 with residence times of up to several hundred ps (at 298 K) 63,64 at some hydration sites. At the same time the density of water around DNA is increased over bulk water 65 since the tetrahedral water coordination in bulk is replaced by more compact geometries as a consequence of hydrogen bonding to the DNA molecule instead. 66 -68 A common measure for the hydration shell around DNA is the number of water molecules that display different properties from bulk water.…”
Section: Water Activity and Dna Conformationmentioning
confidence: 99%
“…Using high-precision densiometric and ultrasonic measurements, Chalikian and co-workers 4 determined the apparent molar volumes and compressibilities of DNA oligomers with varying base compositions and base sequences, and reached some general conclusions about the hydration of B-DNA duplexes: the CG base-pairs are more hydrated than the AT base-pairs and mixed base sequences are less hydrated than either CG or AT B-DNA homopolymers. In agreement with this experimental study, we observed in most studies, independently of base sequence or duplex conformation, the superior hydration of the CG base-pairs in relation to the AT base-pairs; our simulations also showed a higher hydration of the CG and AT pairs of nucleotides in homopolymeric B-DNAs in comparison to B-DNAs with mixed sequences, suggesting that our protocol is able to discriminate B-DNA homoligomers from B-DNA heteroligomers (see Table 5).…”
Section: B-dna Homoligomers Versus B-dna Heteroligomersmentioning
confidence: 99%
“…Many ligands, such as amino acids, drugs or even other nucleotides, interact with nucleic acids either through a water bridge or by replacing structural water molecules bound to specific sites or, most commonly, by both types of contacts. 1 Although the preferential hydration sites of nucleic bases are quite conservative according to comparative crystallographic data, 2 different nucleotide sequences, 3 base compositions, 4 and conformations 5 affect hydration in a very complex manner. In order to understand the function of this type of biomolecule in the cell environment or even inside cell organelles, it is important to investigate nucleic acid hydration sites more extensively, including the dynamics of the first hydration shells, the energetics of water binding, and the role of hydration and ions in nucleic acid conformations and ligand recognition-binding processes as well.…”
Section: Introductionmentioning
confidence: 99%